Quantitative analysis of patient motion in walk-through PET scanner and standard axial field of view pet scanner using infrared-based tracking - Rabia Aziz; Jens Maebe; Florence Marie Muller; Yves D’Asseler; Stefaan Vandenberghe (EJNMMI Physics)
Abstract Background Long-axial field-of-view (LAFOV) Positron Emission Tomography (PET) scanners provide high sensitivity, but throughput is limited because of time-consuming patient positioning. To enhance throughput, a novel Walk-Through PET (WT-PET) scanner has been developed, allowing patients to stand upright, supported by an adjustable headrest and hand supports. This study evaluates the degree of motion in the WT-PET system and compares it with the standard PET-CT. Methods Three studies were conducted with healthy volunteers to estimate motion. The first two studies assessed motion in the WT-PET’s Design I (Study 1) and Design II (Study 2), while the third study compared motion on a standard PET-CT scanner bed (Study 3). Infrared markers placed on the head, shoulders, chest, and abdomen were tracked and processed using image-processing techniques involving thresholding and connected component analysis. Videos were recorded for normal breathing and breath-holding conditions, and 2D centroids were transformed into 3D coordinates using depth information. Results The results shows a significant reduction in motion during breath-holding, especially for the abdomen. Mean motion distances decreased from 2.63 mm to 2.18 mm in Study 1 and from 2.42 mm to 1.67 mm in Study 2. Statistical analysis revealed notable differences in motion between the WT-PET and mCT scanners. The Shapiro-Wilk test indicated non-normal motion distributions in the head, right shoulder, and abdomen for both systems, leading to the use of the Wilcoxon signed-rank test for all markers. Significant differences were found in the right shoulder (p = 0.0266), left shoulder (p = 0.0004) and chest (p < 0.0001) but no significant differences were observed in the head (p = 0.1327) and abdomen (p = 0.8404). Conclusion This study provides a comprehensive analysis of patient motion in a WT-PET scanner with respect to the standard PET. The findings highlight a significant increase in shoulder and chest motion, while the head and abdomen regions showed more stability.